Transcriptome analysis of the brain provides insights into the regulatory mechanism for Coilia nasus migration - Wang, Meiyao (BMC Genomics, 2020)
BACKGROUND: Coilia nasus (C. nasus) is an important anadromous fish species that resides in the Yangtze River of China, and has high ecological and economical value. However, wild resources have suffered from a serious reduction in population, attributed to the over-construction of water conservancy projects, overfishing, and environmental pollution. The Ministry of Agriculture and Rural Affairs of the People’s Republic of China has issued a notice banning the commercial fishing of wild C. nasus in the Yangtze River. Wild C. nasus populations urgently need to recover. A better understanding of C. nasus migration patterns is necessary to maximize the efficiency of conservation efforts. Juvenile C. nasus experience a simultaneous effect of increasing salinity and cold stress during seaward migration, and the brain plays a comprehensive regulatory role during this process. Therefore, to explore the early seaward migration regulation mechanism of juvenile C. nasus, we performed a comparative transcriptome analysis on the brain of juvenile C. nasus under salinity and cold stress simultaneously. RESULTS: Relevant neurotransmitters, receptors, and regulatory proteins from three categories of regulatory pathway play synergistic regulatory roles during the migration process: neuronal signaling, the sensory system, and environmental adaptation. The significant differential expression of growth-related hormones, thyroid receptors, haptoglobin, and prolactin receptors was similar to the results of relevant research on salmonids and steelhead trout. CONCLUSIONS: This study revealed a regulatory network that the brain of juvenile C. nasus constructs during migration, thereby providing basic knowledge on further studies could build on. This study also revealed key regulatory genes similar to salmonids and steelhead trout, thus, this study will lay a theoretical foundation for further study on migration regulation mechanism of anadromous fish species.